Graber: Studi Peluang Bisnis Alternatif Mahasiswa di Kota Medan - Adhitya, Wisnu Rayhan; Sari, Eka Purnama (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to uncover the phenomenon of current students who choose to join Graber as a part-time job besides studying. The study also aims to determine the positive and negative impacts of graber on student academic achievement. This research was conducted in Medan city with student respondents who joined the online transportation company Grab Medan, with a sample of students from four state universities namely Medan State University, North Sumatra University, North Sumatra State Islamic University and Medan State Polytechnic using accidental sampling. Data collection uses questionnaires, and data analysis uses descriptive statistics to uncover the choice of students to become grabers, and t-test comparative analysis to reveal the influence as a graber on student academic achievement between before and after becoming a graber.